Incorporating Individual‐Level Treatment Effects and Outcome Preferences Into Personalized Blood Pressure Target Recommendations - Simon B. Ascher; Richard L. Kravitz; Rebecca Scherzer; Jarett D. Berry; James A. de Lemos; Michelle M. Estrella; Daniel J. Tancredi; Anthony A. Killeen; Joachim H. Ix; Michael G. Shlipak (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background There are no shared decision‐making frameworks for selecting blood pressure (BP) targets for individuals with hypertension. This study addressed whether results from the SPRINT (Systolic Blood Pressure Intervention Trial) could be tailored to individuals using predicted risks and simulated preferences. Methods and Results Among 8202 SPRINT participants, Cox models were developed and internally validated to predict each individual's absolute difference in risk from intensive versus standard BP lowering for cardiovascular events, cognitive impairment, death, and serious adverse events (AEs). Individual treatment effects were combined using simulated preference weights into a net benefit, which represents a weighted sum of risk differences across outcomes. Net benefits were compared among those above versus below the median AE risk. In simulations for which cardiovascular, cognitive, and death events had much greater weight than the AEs of BP lowering, the median net benefit was 3.3 percentage points (interquartile range [IQR], 2.0–5.7), and 100% of participants had a net benefit favoring intensive BP lowering. When simulating benefits and harms to have similar weights, the median net benefit was 0.8 percentage points (IQR, 0.2–2.2), and 87% had a positive net benefit. Compared with participants at lower risk of AEs from BP lowering, those at higher risk had a greater net benefit from intensive BP lowering despite experiencing more AEs (P<0.001 in both simulations). Conclusions Most SPRINT participants had a predicted net benefit that favored intensive BP lowering, but the degree of net benefit varied considerably. Tailoring BP targets using each patient's risks and preferences may provide more refined BP target recommendations.